An introduction to the profession of social work : becoming a change agent - Segal, Elizabeth A. 4 0 16; Gerdes, Karen E.,;Steiner, Sue; 5 (Australia :;Australia : Brooks/Cole Cengage Learning,;Brooks/Cole Cengage Learning, 2010)
Considering a career in social work? Or, simply interested in how these talented and dedicated professionals contribute to society? AN INTRODUCTION TO THE PROFESSION OF SOCIAL WORK: BECOMING A CHANGE AGENT, 3E introduces you to the social-work profession and describing the role of social worker in the social-welfare system. Through case studies, personal stories, and exercises, this social-work text helps you apply the concepts and truly understand what it means to be a social worker.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Social service.;Public welfare.;Social workers.;Human services.;Social problems; 20; 2